The Influence of the Chemical Structures of Chitosan and Acid Dye on the Adsorption Process - Hayet Ben Ali; Salma Besbes Hentati; Salem S. Al-Deyab; Mohamed Rzaigui; M'henni Mohamed Farouk (E-Journal of Chemistry)
The objective of this paper is the study of the influence of the chemical structures of adsorbent and adsorbate on the adsorption process. By using of crab shell chitosan (CC) and deep-pink shrimp chitosan (CP) for removal of acid 183 and AR114 from aqueous solutions, it is shown that CP, which corresponds to the highest molecular weight, is the most efficient adsorbent material. In addition, the best extent of decolorization is obtained for AR 183 that is the smallest molecule. Langmuir model represents the best fit of the experimental data, indicating monolayer coverage of chitosan outer surface. Pseudo-second order kinetic model describes accurately the adsorption processes, suggesting chemical rate limiting steps. The positive values of the enthalpy changes indicated endothermic attachment of dyes to the biomaterials. CP/AR183 system corresponds to the most energetically favorable phenomenon. Besides, desorption of AR from chitosan was found to be very low in acidic aqueous medium for all couples.